Stek Pucuk Pala Tomandin Fakfak (Myristica argentea Warb.) dengan Bahan Stek Asal Semai dan Tanaman Dewasa - Ricardo, Ricardo; Nugroho, Julius; Maturbongs, Rudi A (Cassowary, 2025)
ABSTRACT: Tomandin Fakfak nutmeg (Myristica argentea Warb) is an important source of income for the people in Fakfak. The plantation development of this nutmeg requires knowledge of plant propagation techniques, one of which is through cuttings. This study aims to study the effect of giving commercial auxin (Rootone), and auxin in the form of a mixture of NAA, and IBA on the success of Tomandin Fakfak nutmeg cuttings, both using cutting materials from seedlings and adult plants. The study was designed in a Complete Randomized Design (RAL), with auxin treatments: control (without auxin), Rootone applied in paste form, a quick dip in IBA/NAA solution (1000/500 ppm), and IBA/NAA (2000/1000 ppm). The research was carried out in 2 (two) sets of research, i.e. using cutting material from seedlings and adult plants. The results showed that the propagation of Tomandin Fakfak nutmeg plants through cuttings was prospective to be developed as an alternative plant propagation technique, even though the success was still low. The best treatment of seedling origin shoot cuttings was found in the application IBA/NAA solution (1000/500 ppm), with rooted cuttings of 12.5%. Cuttings of shoots from adult plants are only able to form calluses, with the highest live cuttings (56.25%) in the treatment of IBA/NAA (1000/500 ppm) and IBA/NAA (2000/1000 ppm).